The Battle for Knowledge Management. The Booming Economy in the Spanish University Policy (Foro de Educacion, 2016)
Starting from the collaborative framework established by Community policy in matters of higher education in this paper the objective is to review the changing functions that traditional universities face in the context of a capitalist economy. The article examines from a critical perspective the role that corporate universities have in the construction of a common area of knowledge, and we posit an analysis of the identities established between these two types of organizations. Above all, however, we attempt to dismantle the idea of the subordination of traditional universities to the growing international tensions that could lead us to think that the Spanish university system is facing the search for innovation based on models of academic superiority. Far from showing resistance to corporate practices, the university system of governance is playing a very active role in the consolidation of global economic policies. This study shows that the dynamics of reinforcement and compensation between Bologna and corporate universities not only does not question the new market formulas that these centres of learning make use of, but they are even contributing tools that foster the discursive and managerial confluence of both types of institution.